ANALISIS KUALITAS DAN KEHANDALAN GELOMBANG MIKRO DIGITAL DI TAMPARAK LAYUNG â HAJAK - Saragih, Hoga; Meiraharjo, Bambang (Teknik dan Ilmu Komputer, 2012)
In order to provide the satisfied services for the bandwidth users, network provider need to pay attenuation about telecommunication infrastructures are offered for customers.Â The GMD link Tamparak Layung - Hajak is one of backbone or prime transmission link in Kalimantan. The Analyzing in this paper is purposed to analyze if the existing links are stillÂ accordance with the standardized recommendations by ITU. The design results can be used in reference to determining the use of the device according to the specifications in the development of microwave radio communications with the route Tamparak Layung - Hajak order to take results in accordance with international standardization. In this case refers to the standard used in ITU-R.Â Keywords: microwave, SDH, LOS.